Corrosion mechanisms of mild steel in chloride‐rich atmospheres. Issue 3 (13th August 2015) - de la Fuente, D.; Díaz, I.; Alcántara, J.; Chico, B.; Simancas, J.; Llorente, I.; García‐Delgado, A.; Jiménez, J. A.; Adeva, P.; Morcillo, M.
Abstract : This work analyses the corrosion mechanisms of carbon steel when exposed to marine atmospheres with very different chloride ion deposition rates. Two extreme situations are described, characterized by a "consolidated rust layer" (at relatively low atmospheric salinities), formed by a diffusion‐controlled corrosion mechanism in which the reduction of dissolved oxygen in the aqueous film deposited on the metal is the predominant cathodic reaction, and an "exfoliated rust layer" (at high atmospheric salinities), where the cathodic reaction of hydrogen evolution becomes important, notably accelerating the corrosion process. The research has employed a range of near‐surface and bulk sensitive analytical techniques (SEM/EDS, µXRD, and SEM/µRaman) to characterize the corrosion products and rust layers formed.